Analisis Kecelakaan Lalu Lintas Ruas Jalan Padang - Solok dengan Metode Accident Rate - Wahab, Wilton; Roza, Angelalia; Ramadhani, Markis Febi; Yusnita, Yessy (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
The Padang-Solok road section is one of the national road sections that frequently experiences accidents every year. The aim of this research is to determine the factors that cause accidents on the Jalan Lubuk Paraku Sitinjau Lauik section based on the accident rate, and find out alternative prevention solutions future traffic accidents. This type of research is descriptive research using the Accident Rate method. The factors reviewed are the total number of accidents that occur and the length of the road section studied. An Accident Rate value > 1.0 will be classified as a Black Spot, while a value < 1.0 will be classified as a Black Site. The results of the accident analysis based on the Accident Rate can be identified in three road sections that show a high accident rate, namely more than 1.0. The highest accident rate was on the Panorama 2 – Padang-Solok City Limits road section at 2.37 accidents/km.year. The most dominant factor causing traffic accidents is the human factor. After an inspection was carried out, the brakes failed due to the large number of descents or steep inclines which made the car brakes not function properly. An alternative solution for preventing accidents is to create a temporary stopping place at the Padang - Solok city limits to cool down the engine and car brakes, repair traffic signs that are not yet permanent and create a special brake rescue lane for broken brakes at Panorama 2 and near the rice fields PU Mes.